PEMETAAN POTENSI UNGGULAN INDUSTRI RUMAH TANGGA (HOME INDUSTRY) DI DESA JEDONG KABUPATEN MALANG - Rifky, Rifky Aldila Primasworo; Rahma, Pamela Dinar; Lestari, Eva Ayu (Jurnal Qua Teknika, 2024)
Jedong Village has quite a number of home industries that have the potential to be able to compete outside the village area. There are several home industries that require special development according to the needs and conditions, especially to strengthen the identity of each Jedong village home industry. This home industry also faces several problems, namely the absence of a logo on home industry products, packaging designs for plastic and wrapping paper, business cards that can be given to customers, business banners at production sites. The purpose of this study was to find out the strategy for increasing the superior potential of home industries in Jedong Village, Malang Regency. The method used in this research is SWOT analysis, which is a strategic planning method used to evaluate strengths, weaknesses, opportunities, and threats in a business. The results of the SWOT analysis based on the calculation of the IFAS and EFAS tables. The strategy that must be implemented is to support fast growth policies. Stable Growth Strategy is a strategy to maintain existing growth. Keywords: Home Industry, Strategy, SWOT Analysis